Utilizing Facebook for Teaching Speaking Skills through Student Activities in Recount Texts - Wahyuni, Dewi Sri (Nexus Publishing NXP, 2024)
The study aimed to investigate the implementation of teaching speaking through the description of picture series on Facebook depicting student activities, and to explore student responses to this approach. Participants included a teacher and tenth-grade students, and the research employed a descriptive qualitative design with data gathered from field notes, checklist observations, and questionnaires. Key findings revealed the instructional sequence: initially, the teacher conducted warm-up activities, explained recount texts, and guided students to describe prepared pictures using simple words and short sentences. Subsequently, students practiced speaking individually by presenting the picture series uploaded on Facebook to the class. The results indicated that 60% of students responded positively to this teaching method, expressing interest in learning through describing picture series on Facebook. To enhance this approach, future implications suggest incorporating more interactive elements into Facebook activities, such as peer feedback mechanisms or multimedia resources, to further engage students and foster a collaborative learning environment. Additionally, integrating assessment strategies that align with speaking skills development on social media platforms could provide valuable insights into student progress and instructional effectiveness.